Terapia ocupacional na educação: composição e delineamentos do campo profissional - Souza, Joana Rostirolla Batista de (2021)
Based on the materialistic-historical dialectic as a guide of our posture, method and praxis, we carried out a systematization and analysis of the production of scientific knowledge about occupational therapy in education; critical development of concepts that are central to this field; and historical positioning in this respect, having as a horizon the recognition of the research topic composing this study – the professional practice of occupational therapists in Brazilian basic education. To map the professional field of occupational therapy in Brazilian basic education and learn the professional activities of occupational therapists connected directly to schools or the educational sector in general, we collected data in two steps. The first one was the conduction of an online survey widely disclosed to the professional category, obtaining 74 valid responses to a questionnaire. The results revealed the existence of the professional field of occupational therapy in basic education in the country and that this began mainly at the turn of the century, involving occupational therapists who became active in schools and/or educational sector by various means: working as freelancers, both through home visits and treating individual patients at their schools; establishment of clinics that rendered services to schools; provision of services by people connected to the health, social assistance or socio-legal sectors, developing professional actions in schools; teaching of occupational therapy in schools, hired directly by or working through municipal or state education secretariats; and also situations not fitting in any of these profiles. The second source of data was in-depth interviews with 15 occupational therapists involved in education selected from the respondents to the survey. Together the information indicated that independently of the sector (public or private) or the structure for organization of the occupational therapy activity, the referral of students to these services is generally forwarded by teachers, and the most evident guiding principle is inclusion in terms of special education. In the public sector, the sub-area circumscribes a nationally disarticulated field of actions, inserted randomly in local educational policies. The respondents expressed critiques of the format of their work, actively seeking to expand dialog with schools about possible contributions. The specificity of the work involves the mastery of the activities and their interaction with the routine experienced by, in great majority, children in schools with the leading strategy being individual treatment highly aligned with the functional perspective and employing varied tools, resources and technologies. Through membership in professional teams there is a notable effort to compose caregiving networks devoted to the subjects who seek these services. Recent social and political pressures have shed light on what is interpreted as the need of professionals from the field of rehabilitation to support supposedly “unprepared” teachers to meet certain demands. The problem is being addressed without proper articulation, and the response offered is limited to individual, palliative action. We propose that the horizon to be pursued is marked by the possibilities of actions of occupational therapists directed to a formal education that is public, diverse, radically inclusive and hence democratic, that provides full development and preparation to exercise citizenship endowed with all the tools necessary for well-being.